Re-Turn to Practice: An Introductory Essay - Miettinen, Reijo; Samra-Fredericks, Dalvir; Yanow, Dvora (Organization studies, 2009)
The study of practices has a long theoretical history and draws on a wide range of methods. This introductory essay sets the stage for the five articles presented in this Special Issue by explaining its background and providing one narrative of the theoretical background on which both its editors and the authors of its articles, in one way or another, draw and to which the latter make explicit or implicit reference.